Transluminal balloon angioplasty and stenting of coronary arteries after prior orthotopic heart transplantation: a case report - A. A. Bapinaev; A. A. Bapinaeva; I. K. Tkhabisimova; A. R. Kogotizhev (Российский кардиологический журнал, 2024)
Introduction. Today, heart failure (HF) is the most common natural outcome of diseases that are not diagnosed and treated in time. Despite the advances in cardiovascular pharmacotherapy, orthotopic heart transplantation is a generally recognized gold standard for the treatment of end-stage heart failure.Brief description. The article describes a 55-year-old male patient admitted to the Cardiology Dispensary (Kabardino-Balkarian Republic) with a clinical picture of non-ST segment elevation acute coronary syndrome (ACS). Earlier in 2017, the patient underwent orthotopic heart transplantation (OHT) for end-stage HF due to dilated cardiomyopathy. Hypertension was registered 2,5 years after surgery, and clinical manifestations of HF were registered for 5 years. In 2024, coronary angiography revealed subtotal stenosis of 95% in the middle segment of the anterior descending artery. Intraoperatively, the consensus assessed the risk and made a decision on surgical endovascular treatment of the stenosis. The postoperative period was uneventful.Discussion. The presented case is an example of timely diagnosis of coronary artery disease in a transplanted heart and successful transluminal balloon angioplasty and stenting of the anterior descending artery.